Effects of a n-3 polyunsaturated fatty acid-enriched diet on embryo production in dairy cows. Issue 1 (July 2019) - Freret, S; Oseikria, M; Bourhis, D Le; Desmarchais, A; Briant, E; Desnoes, O; Dupont, M; Le Berre, L; Ghazouani, O; Bertevello, P S; Teixeira-Gomes, A P; Labas, V; et al.
Abstract : Beneficial effects of n-3 polyunsaturated fatty acid (PUFA) supplementation on dairy cow reproduction have been previously reported. The objectives of the present study were to assess whether n-3 PUFA supplementation would affect in vitro embryo production (IVP) after ovarian stimulation. Holstein cows received a diet with 1% dry matter supplementation of either n-3 PUFA ( n = 18, microencapsulated fish oil) or a control, n-6 PUFA ( n = 19, microencapsulated soy oil). Both plasma and follicular fluid FA composition showed integration of total PUFA through the diet. All cows underwent an IVP protocol consisting of ovarian stimulation, ultrasound-guided transvaginal oocyte retrieval (ovum pick-up, OPU, five per cow) followed by in vitro maturation, fertilisation and 7 days of embryo development. A tendency toward an increase in the blastocyst rate (diet effect, P = 0.0865) was observed in n-3 cows, with 49.6 ± 5.5% vs 42.3 ± 5.5% in control n-6 cows. A significant increase (diet effect, P = 0.0217) in the good-quality blastocyst rate (freezable blastocysts) was reported in n-3 cows (42.2 ± 7.7%) compared to control n-6 cows (32.7 ± 7.7%). A significant difference in lipid composition was shown in the oocytes recovered by OPU from n-3 and n-6 treated cows, by intact single-oocyte MALDI-TOF mass spectrometry. The 42 differentially abundant identified lipids were mainly involved in cell membrane structure. In conclusion, n-3 PUFA supplementation enhanced oocyte quality and modified their lipid composition. Further studies are necessary to investigate the potential link of these lipid modifications with enhanced oocyte quality.